YjbH Solubility Controls Spx in Staphylococcus aureus: Implication for MazEF Toxin-Antitoxin System Regulation - Panasenko, Olesya O.; Bezrukov, Fedor; Komarynets, Olga; Renzoni, Adriana (Frontiers in Microbiology, 2020)
Bacterial cells respond to environmental stresses by modulating their gene expression and adjusting their proteome. In Staphylococcus aureus, selective degradation by ClpP protease eliminates damaged proteins and regulates the abundance of functional proteins such as many important stress-induced transcriptional regulators. Degradation by ClpP requires the unfolding activity of partner Clp ATPases, such as ClpX and ClpC, and assistance of substrate-specific adaptor proteins such as YjbH and TrfA. Herein, we demonstrated that YjbH is aggregated in response to growth stress stimuli, such as oxidative and antibiotic stresses. In consequence, its function as an adaptor protein is compromised. YjbH controls the degradation of the stress-induced transcriptional regulator, Spx. Aggregated YjbH cannot assist Spx degradation, which results in Spx accumulation. We discovered that depending on the stress stimulus, Spx can be soluble or insoluble, and, consequently, transcriptionally active or inactive. Therefore, Spx accumulation and solubility are key components governing activation of Spx-dependent genes. Spx positively regulates expression of a ClpCP adaptor protein TrfA. TrfA in turn is required for degradation of MazE antitoxin, the unstable component of the MazEF toxin-antitoxin system, that neutralizes the endoribonuclease activity of MazF toxin. Bacterial toxin-antitoxin systems are associated with dormancy and tolerance to antibiotics that are related to chronic and relapsing infections, and it is at present a key unresolved problem in medicine. MazF activity was linked to growth stasis, yet the precise environmental signals that trigger MazE degradation and MazF activation are poorly understood. Here we propose a model where YjbH serves as a sensor of environmental stresses for downstream regulation of MazEF activity. YjbH aggregation, soluble Spx, and TrfA, coordinately control MazE antitoxin levels and consequently MazF toxin activity. This model implies that certain stress conditions culminate in modulation of MazF activity resulting in growth stasis during in vivo infections